MODEL INVESTIGASI KELOMPOK DENGAN TEKNIK ADU ARGUMEN SEBAGAI UPAYA PENINGKATAN KOMPETENSI PEDAGOGIK CALON GURU BAHASA INDONESIA - Zulaeha, Ida (Universitas Negeri Semarang, 2015)
This research was conducted with the aim of describing the needs development of the group investigation model with argument argue techniques that can improve pedagogical competence the students of Indonesian teachers candidates course participants of micro teaching learning than then generate a model of learning micro lectures is used as an effort to improve pedagogical competence Indonesian students teachers candidates in planning and implement innovative learning. The research carried out by using a design research and development. The need for the development of the model include implementing the objectives and characteristics of learning in secondary education, determine appropriate instructional design, practice basic skills in creative and innovative teaching, practice of managing large and small classes, adjust instructional practices with students and the school environment, practices to manage and resolve various problems when teaching practice, and evaluate appropriate learning criterion. Sintakmatik models investigation group with techniques argue argument include giving problem, exploration of response, realization of response, discussion and analysis of the learning process, and revision activities.